1998
DOI: 10.1007/s001340050532
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical function in patients with ruptured aneurysm of the abdominal aorta

Abstract: In the patients studied with ruptured aneurysm of the abdominal aorta, adrenocortical response was comparable to that in other groups of critically ill patients with similar severity of illness. High cortisol levels were associated with mortality. One patient did not meet the criteria for normal adrenocortical function but survival without steroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
3
22
1
2
Order By: Relevance
“…It is noteworthy that the mean admission cortisol concentration in patients with sepsis was 1532 nmol/l, whereas in patients after repair of ruptured abdominal aneurysm, mean concentration was 381 nmol/l. Other studies of septic patients have found lower initial mean cortisol concentrations (730 [35], 938 [34], 1016 [17], and 1236 nmol/l [13]) and a much higher concentration (760 nmol/l [36]) after ruptured abdominal aortic aneurysm. Jurney and colleagues [13] found that cortisol concentrations in patients with gastrointestinal bleeding were less than in patients with respiratory failure or sepsis.…”
Section: Patients With Abnormally Low Endocrine Valuesmentioning
confidence: 99%
“…It is noteworthy that the mean admission cortisol concentration in patients with sepsis was 1532 nmol/l, whereas in patients after repair of ruptured abdominal aneurysm, mean concentration was 381 nmol/l. Other studies of septic patients have found lower initial mean cortisol concentrations (730 [35], 938 [34], 1016 [17], and 1236 nmol/l [13]) and a much higher concentration (760 nmol/l [36]) after ruptured abdominal aortic aneurysm. Jurney and colleagues [13] found that cortisol concentrations in patients with gastrointestinal bleeding were less than in patients with respiratory failure or sepsis.…”
Section: Patients With Abnormally Low Endocrine Valuesmentioning
confidence: 99%
“…Etomidate-induced adrenal cortical dysfunction is an issue of some import, because this drug is being used as an induction agent with increasing frequency, particularly in patients with compromised cardiovascular systems or hypovolemia. However, in the report by Braams et al [1], there is no difference in mortality between those patients receiving and those not receiving etomidate for induction. Because patients with ruptured abdominal aortic aneurysms are a particularly high risk group, the present findings are comforting.…”
mentioning
confidence: 65%
“…In this issue of Intensive Care Medicine, Braams et al [1], report findings from an investigation of adrenal cortical function during the first 24 h after admission to an intensive care unit following operation for repair of ruptured abdominal aortic aneurysm. The authors measured plasma cortisol levels at baseline and 60 min after stimulation with exogenous ACTH.…”
mentioning
confidence: 99%
“…In this critically ill patient population it is difficult to demonstrate a relative adrenal insufficiency by measurement of`basal' plasma cortisol levels or by a stimulation test using synthetic ACTH [2,4,10]. Two studies suggest a correlation between higher cortisol levels and decreased chance of survival: 1129 nonsurvivors at 1030 nmol/l versus 829 survivors at 730 nmol/l [2,10]. Elevated cortisol levels have been measured in intensive care patients by most investigators (Fig.…”
Section: Discussionmentioning
confidence: 99%